Role of length specificity, velocity specificity and neural adaptations in strength training - Ismail, Ahmad Naim (2012)
A very common finding among many training studies is that the increase in weightlifting strength is greater than the increase seen in isometric strength. Most are in view that this is the result of training and testing specificity. However the exact underlying mechanism that is responsible for the discrepancy has yet to be explained. The three studies of this thesis examine the explanation behind the discrepancy between the increases seen in weight-lifting strength compared to isometric strength after resistance training. The first study was to look into the role of learning. Thirty two students completed the training. The subjects underwent four weeks of unilateral leg extension training, three times per week,three sets of eight lifts. One leg was chosen arbitrarily for the training. The contralateral leg, which was not trained, acted as a control. Subjects performed at a steady pace. The result showed that the lesser experienced subjects showed a significant improvement in training weights lifted which illustrated that weight-lifting is very much a skill based task. The second study was to look into length specificity and velocity specificity. Eighteen subjects completed the study. Subjects completed eight weeks of leg extension training,three times per week,four sets of six to eight lifts. One leg was arbitrarily assigned to perform the dynamic training. Isometric strength measured in the strength-testing chair. Measurements of isometric strength at 15° intervals from 60° to 105° of knee flexion using isokinetic dynamometer. Isokinetic strength testing was also measured at velocities of 45° s-1, 180° s-1 and 300° s-1. A non-significant 6% increase of isometric maximum voluntary contraction (MVC) at 90° was found and between 13% and 19%.Increases of isometric torque were found at all angles measured. The training resulted in increases in the isokinetic torque at all velocities for the trained leg. The result has shown no evidence to any length or velocity specific adaptations. The third study was to look into whether there is any increase in neural activity during dynamic contractions in explaining the discrepancy between the increase in training weights and MVC. Seven male subjects participated in this study. Subjects were trained three times per week for four weeks, 80 - 85% of 1RM for three sets. One leg was chosen randomly. Subjects performed dynamic leg extension on a leg extension machine. The electromyogram (EMG) activity of vastus lateralis and biceps femoris was recorded for the training and control leg during all testing. There were no significant differences in terms of MVC force produced between the training chair and the strength testing chair. The EMG data showed there was no significant change in the EMG activity of the vastus lateralis of the trained leg after training. There was a reduction in EMG activity of the hamstring during the 1 RM post training but was not significant. The results of the study have shown that there is no increase in neural activity which would explain the difference between the increase in training weights and MVC. Nor were there any significant changes in co-activation of the hamstring. The discrepancy seen in the large increase in the weight lifting strength as compared to isometric strength cannot be accounted for by the angle specificity and velocity specificity factors. There is also no increase in neural activity which would explain the difference between the increase in training weights and MVC. Nor were there any significant changes in co-activation of the hamstring, consequently the discrepancy remains unexplained.